PEMBERDAYAAN PEREMPUAN MELALUI PEMBUDIDAYAAN TANAMAN SAYURAN DALAM POT BERBASIS APLIKASI TEKNOLOGI BOKASHI ECENG GONDOK - Siti Zubaidah, Dan Syahrudin, Gusti Irya Ichriani Kambang Vetrani Asie (Buletin Udayana Mengabdi, 2013)
Vegetables cultivation in the pot based on Eichhornia crassipes bokashi technology application is the activity to empower women synergized with the natural resources around them. The purposed of IbM program implementation were (1) empower and provide skills to the women group in order to utilize of natural resources (Eichhornia crassipes, sawdust and alluvial soil) and obtain vitamines, minerals and fiber for households through the vegetables cultivation in the pot and utilization of Eichhornia crassipes bokashi as growing mixture media; (2) as effort to save on household spending and to creating entrepreneurship. This program was carried out with two groups of women (the RW I women group and RW II women group) from Cemara Labat, Palangka Raya, Central of Kalimantan. Socialization, training and coaching about cultivation of vegetables in the pot and making of Eichhornia crassipes bokashi has given the ability and skills to the women group for utilizing natural resources around them. This IbM programme has sustainability. It is caused the women groups from RW I and RW II Cemara Labat want to continue planting vegetables in the pot using Eichhornia crassipes bokashi, to meet needs of household vegetables daily and it has raised a family entrepreneurship.